FAKTOR FAKTOR YANG MEMPENGARUHI KEPUASAN NASABAH PADA PELAYANAN CUSTOMER SERVICE BPD KALTIM CABANG UTAMA SAMARINDA - Makahanap, Agus Shella (EKONOMIA, 2013)
The purpose of this research is to discover the influence of service quality and which variable that has major influence towards customer satisfaction of BPD Kaltim’s customer service. The principle theory of this research is marketing management.Based on teoritic, hypothesis of this research that service quality variabels don’t influence significantly toward customer satisfaction of BPD Kaltim’s customer service.Multiple regression analysis is used F test and t test at probability = 0,05. Result of the research showed that five variables of service quality don’t influence significantly toward customer satisfaction of BPD Kaltim’s customer service.The calculation result showed that responsiveness variable has negative influence towards customer satisfaction.